The Implications of Patriarchal Culture on the Desire to Marry - Ratri Febri Nurfitri; Ahyat Habibi (Sekolah Tinggi Agama Islam Sumatera Medan, 2026)
This study aims to analyze patriarchal culture from the perspective of female students at the Imam Syafi’i Islamic College in Jember and its implications for their desire to marry. The study was motivated by the persistence of patriarchal practices in domestic relationships, which often intersect with Muslim women’s religious understanding. The study employs a qualitative approach, collecting data through open-ended questionnaires administered to 15 active female students, supplemented by a literature review. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data presentation, and drawing conclusions. The results indicate that patriarchal culture is manifested in the subordination of women, gender stereotypes, and unequal division of domestic labor—factors that potentially impose a double burden on women. However, the respondents did not view these practices as part of Islamic teachings but rather as social constructs of society. The main findings of the study indicate that the implications of patriarchal culture on the desire to marry are divided into three trends: a decrease in the desire to marry, a hesitant attitude, and a stable desire to marry. These differences are influenced by the respondents’ social experiences and their normative understanding of Islam.